Comportamento inovativo das pequenas e médias empresas industriais brasileiras: uma análise em nível da firma - Hamberger, Paula Andréa do Valle (2014)
The purpose of this thesis is to contribute to the Brazilian literature on the innovative behavior of small and medium enterprises. The focus is the sectoral analysis to identify if the Brazilian manufacturing SMEs conform to sectoral patterns and if these patterns influence the innovative activities of the firms. This empirical work is composed of three different stages. The first stage refers to the investigation by size and sector using descriptive analysis of the innovative activities of the Brazilian SMEs by labor employed (for PINTEC-2008 and PINTEC-2011) and by sectoral patterns (for PINTEC-2008), according to Pavitt´s taxonomy. The second stage made use of a nonparametric methodology applied to the PINTEC-2008´s microdata to distinguish sectoral patterns for SMEs identifying if they influence the innovative behavior of small and medium firms and at last if Pavitt´s taxonomy is applicable. The third stage drew upon the logistic regression method applied to the PINTEC´s microdata for the period of 2006 to 2008 and 2009 to 2011, to verify if the sectoral technological patterns are significant determinants of the SMEs´ innovative process. That was analyzed for different types of innovative activities, such as: innovative firms, product innovators, process innovators, product and process innovators, highly innovative firms, organizational innovators and marketing innovators. Moreover, identifying if these influences differ from those affecting big firms. The results obtained reveal that sectoral dynamics are relevant to the innovative behavior of SMEs, similarly to what happens to large companies.